Effect of yoga on autonomic functions in medical students: a pilot study - HC, Shashikiran; Shetty, Prashanth; R, Chethan Kumar; Shetty, Shivaprasad (International Journal of Research in Medical Sciences, 2017)
Background: Stress and anxiety being the major contributors of morbidity, leads to many chronic diseases and is known to invariably decrease the quality of life and even life span. Autonomic Nervous System (ANS), a part of the peripheral nervous system that controls the visceral system, functioning largely under the level of consciousness, capable of being influenced by the psychological factors and influences the physiological processes happening in the body. Non-pharmacological therapies play a major role to relieve stress and anxiety of which yoga takes first place compared to pharmacological treatment. Present study adopts a systematic approach in comparing the effects of practicing yoga for one year with novices on autonomic and respiratory variables. Methods: We recruited sixty subjects from the Sri Dharmasthala Manjunatheshwara College of Naturopathy & Yogic Sciences, Ujire and their mean age group is 18.8 ± 2.3 fulfilling the selection criteria, after they gave written consent to participate. They were divided into 2 groups based on their experience of practicing yoga. Each group consisted of 30 subjects. Group 1 includes participants with no experience in yoga (Novices group) and Group 2 (Yoga group) includes individuals with one year experience of practicing yoga. Each group consists of 17 males and 13 females respectively. The study was approved by the ethical review committee. Informed written consent was obtained from all subjects. All students were subjected to Onetime Assessment for autonomic variables and respiration at base line and during deep breathing. Results: In our study we observed that there was a significant decrease in heart rate (P = 0.004***) following intervention in yoga group compared to novice group. There was a significant difference in Respiration rate (P = 0.003***) and Mean RR (P = 0.002***) which indicate increase parasympathetic activity in yoga group compared to novice group. There is also a significant difference in time domain parameter PNN50 (P = 0.030*) which is an indicator of parasympathetic activity. There was no significant difference in other time domain and frequency domain parameter. Conclusion: Practicing yoga regularly for one year can reduce the physiological arousal and develops the ability to adapt to a demanding situation.